Angiotensin II augments renal vascular smooth muscle soluble GC expression via an AT1 receptor–forkhead box subclass O transcription factor signalling axis. (9th June 2021) - Galley, Joseph C.; Hahn, Scott A.; Miller, Megan P.; Durgin, Brittany G.; Jackson, Edwin K.; Stocker, Sean D.; Straub, Adam C.
Abstract : Background and Purpose: Reduced renal blood flow triggers activation of the renin‐angiotensin‐aldosterone system (RAAS) leading to renovascular hypertension. Renal vascular smooth muscle expression of the NO receptor, soluble GC (sGC), modulates the vasodilator response needed to control renal vascular tone and blood flow. Here, we tested if angiotensin II (Ang II) affects sGC expression via an AT1 receptor‐forkhead box subclass O (FoxO) transcription factor dependent mechanism. Experimental Approach: Using a murine two‐kidney‐one‐clip (2K1C) renovascular hypertension model, we measured renal artery vasodilatory function and sGC expression. Additionally, we conducted cell culture studies using rat renal pre‐glomerular smooth muscle cells (RPGSMCs) to test the in vitro mechanistic effects of Ang II treatment on sGC expression and downstream function. Key Results: Contralateral, unclipped renal arteries in 2K1C mice showed increased NO‐dependent vasorelaxation compared to sham control mice. Immunofluorescence studies revealed increased sGC protein expression in 2K1C contralateral renal arteries over sham controls. RPGSMCs treated with Ang II caused a significant up‐regulation of sGC mRNA and protein expression as well as downstream sGC‐dependent signalling. Ang II signalling effects on sGC expression occurred through an AT1 receptor and FoxO transcription factor‐dependent mechanism at both the mRNA and protein expression levels. Conclusion and Implications: Renal artery smooth muscle, in vivo and in vitro, up‐regulates expression of sGC following RAAS activity. In both cases, up‐regulation of sGC leads to increased downstream cGMP signalling, suggesting a previously unrecognized protective mechanism to improve renal blood flow in the uninjured contralateral renal artery. LINKED ARTICLES: This article is part of a themed issue on cGMP Signalling in Cell Growth and Survival. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v179.11/issuetoc Abstract : Renal artery stenosis causes elevated circulating angiotensin II. This, in turn, leads to contraction and hypertrophy of smooth muscle and elevated BP. Additionally, soluble GC (sGC) expression and cGMP in the non‐stenotic renal artery increases allowing for increased blood flow to the healthy kidney.